Molecular Detection of Aflatoxin Producing Strains of Aspergillus Flavus from Peanut (Arachis Hypogaea) - Adeela Hussain; Awais Afzal; Muhammad Irfan; Kauser Abdulla Malik (Turkish Journal of Agriculture: Food Science and Technology)
Aflatoxins are the potential carcinogens produced as secondary metabolites by Aspergillus flavus. They have the ability to contaminate large number of food which ultimately affect the human population. Malt extract agar was selected for the growth of control stains of fungus. The aim of the study was to develop a reliable and quick method for the detection of aflatoxin producing strains in peanuts by using molecular approaches. Total 80 samples of infected peanuts were collected from four different cities of Punjab and checked for their aflatoxin contamination. For aflatoxin detection, three target genes nor1, ver1 and aflR were selected which was involved in the aflatoxin biosynthesis. In all examined cases, 24 out of 80 (30%) samples successfully amplified all three genes indicating aflatoxigenic activity. Discrimination between aflatoxigenic and non-aflatoxigenic strains were also determined on the basis of amplification of these three target DNA fragments. In this study, it was also demonstrated that only specific strains were able to produce the aflatoxin contamination in peanuts.